Treatment of intermittently flowing wastewaters - (:unkn) unknown (Marcel Dekker Inc., 1998)
Conventional biological treatment of intermittently flowing wastewaters is one of the significant problems of regions having seasonal activities. A system consisting of an downflow aerated packed reactor (DAPR) followed by inclined tube settler (ITS) was tried to overcome the difficulties for the above mentioned wastes. The DAPR-ITS system can be regarded as a combination of activated sludge and trickling filter process followed by a high rate sedimentation unit (ITS). Three different no-feed periods ranging from 3 to 26 weeks were used to characterize the off-season activities. After this no-feed period the system was started using different flow rates. The performance of the system was evaluated using chemical oxygen demand (COD), biochemical oxygen demand (BOD), nitrogen (N), phosphate (P) and total suspended solids (TSS) parameters. The results showed that DAPR-ITS achieved about 80% COD removal efficiency from the time of starting the system and reached steady state conditions within a few days. The removal efficiencies of other parameters had similar trends as COD Thus, DAPR-ITS system has been proven to be a satisfactory method for intermittently flowing wastewaters.
Keywords: Intermittently flowing wastewaters; Packed column; Sedimentation